2015
DOI: 10.1142/s0219887815500334
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry analysis of the Klein–Gordon equation in Bianchi I spacetimes

Abstract: In this work we perform the symmetry classification of the Klein Gordon equation in Bianchi I spacetime. We apply a geometric method which relates the Lie symmetries of the Klein Gordon equation with the conformal algebra of the underlying geometry. Furthermore, we prove that the Lie symmetries which follow from the conformal algebra are also and Noether symmetries for the Klein Gordon equation. We use these resutls in order to determine all the potentials in which the Klein Gordon admits Lie and Noether symme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…From (26) it follows that T ,tt = 0, that is T (t) = T 0 + T 1 t, while from (26) we have that Z A = ψT 1 tY A or Z A = Y A and T 1 . Condition (27) provides an infinite number of trivial symmetries, which is a well-known result for the heat equation. Thus, from Theorem 1 follows:…”
Section: Theoremmentioning
confidence: 82%
“…From (26) it follows that T ,tt = 0, that is T (t) = T 0 + T 1 t, while from (26) we have that Z A = ψT 1 tY A or Z A = Y A and T 1 . Condition (27) provides an infinite number of trivial symmetries, which is a well-known result for the heat equation. Thus, from Theorem 1 follows:…”
Section: Theoremmentioning
confidence: 82%
“…It was shown that the Lie and Noether symmetries of that system are related with the special projective algebra of the underlying space. This geometric approach has been extended to the determination of the Lie and Noether point symmetries of some families of partial differential equations [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the Lie and the Noether symmetries of the WDW equation we will follow the results of [39,40] which relate the point symmetries of the WDW equation with the conformal algebra of the space which defines the Laplace operator. This means that we can separate the problem in two steps: (a) we will study the conformal algebra of the minisuperspace and (b) we will determine the unknown potential.…”
Section: Lie Symmetries Of the Wdw Equationmentioning
confidence: 99%
“…In [39,40], it has been shown how to extract the conservation laws and compute the Noether integrals for a given classical Lagrangian from the Lie symmetries of the WDW equation. In this section, for each Lie group of transformations in terms of which the WDW Eq.…”
Section: Conservation Laws and Analytical Solutions Of The Field Equamentioning
confidence: 99%